Analysis of Emotional Dissonance and Burnout on Sales Aggressiveness Among Sales Promoters at PT X - Septi Revalinda; Kartika Nuradina; Recky Recky; Pras Rendy (International Journal of Marketing & Human Resource Research, 2026)
Sales staff in the retail sector are required to meet sales targets while providing quality service to customers. These demands can lead to emotional dissonance, a condition in which sales staff must display emotions that differ from their true feelings, which has the potential to trigger burnout and increase the likelihood of aggressive sales behavior. This study aims to analyze the relationship between emotional dissonance, burnout, and sales aggression among Sales Promotion Girls (SPG) and Sales Promotion Men (SPM) at PT X. The study employs a quantitative approach using an explanatory survey method. The sample consisted of 126 respondents selected using simple random sampling. Data were collected via a Likert-scale questionnaire and analyzed using descriptive statistics and Spearman’s rank correlation test, as the data were not normally distributed. The results of the study indicate that emotional dissonance, burnout, and sales aggression generally fall into the low category, with mean scores of 33.15, 40.16, and 29.73, respectively. Nevertheless, the correlation test results show a positive and significant relationship among the variables. Emotional dissonance has a strong relationship with burnout (ρ = 0.776; p < 0.001) and a very strong relationship with sales aggression (ρ = 0.933; p < 0.001), while burnout also has a strong relationship with sales aggression (ρ = 0.796; p < 0.001). These findings indicate that the higher the level of emotional dissonance experienced by salespeople, the higher their levels of burnout and tendency toward sales aggression. Therefore, companies need to strengthen organizational support, create a conducive work environment, and improve the management of employees’ psychological well-being to minimize burnout and aggressive sales behavior while enhancing the quality of customer service